The Effect of Sustainability Reporting Practices on Investor Confidence and Corporate Financial Performance in Listed Companies - Eko Sudarmanto; Yeni Priatna Sari; Metyria Imelda Hutabarat; Kadambaeva Charos Masharipovna (International Forum of Researchers and Lecturers, 2024)
Sustainability reporting has become a critical tool for enhancing corporate transparency, building investor confidence, and improving financial performance. This study explores the relationship between detailed sustainability reporting practices and investor confidence, as well as their impact on corporate financial outcomes, particularly Return on Assets (ROA). The research utilized content analysis of sustainability reports from listed companies, focusing on the level of detail and transparency in the reports, and conducted an investor perception survey to assess their trust and confidence in companies based on the sustainability disclosures. The findings reveal a positive correlation between comprehensive sustainability reporting and higher levels of investor confidence, with companies that provide transparent and detailed reports outperforming those with minimal disclosures in terms of financial performance. Companies that effectively communicate their environmental, social, and governance (ESG) practices through clear sustainability reports tend to experience improved operational efficiency, increased profitability, and higher ROA. The study also highlights that sustainability reporting is not merely a tool for corporate responsibility but serves as a strategic advantage in attracting investment and achieving long-term financial success. The research recommends that companies invest in enhancing their sustainability disclosures to attract more investors and improve financial health. Additionally, policymakers should consider mandating detailed sustainability reporting to improve market transparency. Future research could focus on examining the long-term effects of sustainability reporting on investor behavior and extend the study to different industries and markets to further understand the role of sustainability disclosures in shaping corporate performance.